Genes polymorphism of surfactant protein B and respiratory morbidity in preschoolers - Mazulov, O.; Yablon, O. (Journal of Education, Health and Sport, 2017)
There was a prospective single-center study of 50 prematurely born children (25 males and 25 females, mean gestational age 31.6 ± 2.6 weeks, mean body weight at birth 1743.4 ± 454.3 g) conducted in Vinnytsya Children’s Regional Hospital during 2010-2015. At the age of 5.2 ± 0.7 years children were divided on a several groups: children diagnosed with asthma - 9 (18%), children diagnosed with recurrent episodes of obstructive bronchitis (recurrent wheezing) - 18 (36%), children diagnosed with bronchopulmonary dysplasia - 8 (16%) and 15 children without respiratory diseases (30%). As a result of Single nucleotide polymorphism (SNP) investigation in surfactant protein B C1580T locus a several sequences were evaluated and explored: CC in 17 (34%) of patients, a TT sequence of nucleotides in 12 (24%) of patients, and CT nucleotide sequence was observed in 21 (42%) children. Odds ratio found that the nucleotide sequence CC might be a predictive value of recurrent bronchial obstructions, nucleotide sequence TT more often observed in patients with asthma, and the presence of CT nucleotide sequence in polymorphic locus of gene of surfactant protein B C1580T might have a positive prognostic value regarding the absence of chronic bronchopulmonary diseases in children.